World Oil Prices and Exchange Rates on Islamic Banking Risks - Hadi Ryandono, Muhamad Nafik; Imron, Mochamad Ali; Wildan, Muhammad Alkirom (International Journal of Energy Economics and Policy, 2022)
Islamic banking risks are influenced by many factors, facing internal and external banking risks. In this study, the internal banking risks are represented by Credit risk as measured by Non-Performing Financing (NPF) and liquidity risks as measured by Financing to Deposit Ratio (FDR). At the same time, world oil prices and exchange rates represent the external banking risks. World oil price data is obtained from OPEC Price, and exchange rate data is obtained from the Pacific Exchange Rate Service. While the data from NPF and FDR is obtained from BI Statistics of Sharia Banking. The results of this study found that world oil prices have a significant effect on credit risk and liquidity risk in Islamic banking. In contrast, the exchange rate only has a significant effect on credit risk in Islamic banking.